Spanish theatre 1920-1995 : strategies in protest and imagination. - Delgado, Maria M. (Contemporary theatre review, 1998)
Beginning with a reassessment of the 1920s and 30s, this text looks beyond a consideration of just the most successful Spanish playwrights of the time, and discusses also the work of directors, theorists, actors and designers.